Manhaj Muʿjam al-Furūq al-Lughawiyyah li-Abī Hilāl al-ʿAskarī - Adib Kurniawan (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2015)
In its general sense, a dictionary refers to any systematically organized list of words from a language, arranged according to a particular method and accompanied by explanations of their literal or figurative meanings as well as their various usages. Dictionaries are indispensable resources for language learners because an individual's vocabulary is naturally limited by the scope of his or her knowledge and experience. Among the many types of dictionaries is Al-Furūq al-Lughawiyyah by Abū Hilāl al-ʿAskarī, which helps readers identify the subtle semantic distinctions between words that are commonly regarded as synonyms. At the same time, it assists users in selecting the most precise lexical item to express the intended meaning with clarity and accuracy. This dictionary is considered one of the most valuable references for investigating ambiguous words, particularly in the Arabic language. It offers a variety of features designed to facilitate the search for word meanings. This article aims to analyze the methodology employed in Al-Furūq al-Lughawiyyah by Abū Hilāl al-ʿAskarī, particularly its semantic or thematic arrangement of lexical entries. Such an arrangement enables users to identify one or more words corresponding to a specific concept. The dictionary also serves several important purposes, including supporting translation, facilitating academic research, assisting scholars engaged in the critical editing of classical Arabic texts, and helping specialists develop terminology for the sciences and the arts. The article begins with a brief overview of the dictionary's historical background, contents, style, and primary objectives, followed by a discussion of selected explanations, its distinctive features, and its limitations.